Management of appendicitis in a De Garengeot hernia: Lockwood approach. Issue 7 (6th July 2022) - Julien, Benjamin; Huang, Yeqian; Ooi, Wei Ling; Beck, Matthew
Abstract : A De Garengeot hernia is a femoral hernia containing the vermiform appendix. This extremely rare hernia is associated with appendicitis and the risk of perforation and abscess formation. Given limited data, it poses both diagnostic and management difficulties. While management is generally surgical, questions remain about the best operative approach, indications for appendicectomy and optimum hernia repair technique. We describe a case of acute appendicitis within a De Garengeot hernia that was managed with an open appendicectomy via a Lockwood incision. This case helps to illustrate the management considerations present for this rare clinical pathology and describes a method to effectively identify the hernia and resect the appendix.